“Efecto de las fases lunares en el rendimiento del cultivo de lechuga variedad great lakes 659, bajo las condiciones de agroecológicas de la provincia de Lamas” - Mendoza Cabanillas, Sarah Beatriz (2015)
The -present research -a-imed to evaluate the -agronomic performance of growing tettuce variety Great takes 659 according to the fourionar phases in the dfstrict andptovince of lamas, atso the most appropriate tunar phase ana itS influence wa$ determinad in performance ancfprofitabifitY ofthe crop. The research was concfuctedon the grounds of fundo '"The Pacific~· owned by Mr. Jorge luis Petaez Rivera, pofiticaUy located in the dístrict and .province of lamas, department of San Martín. Statisfical Des"ign. randomized complete. block (RCBD) With.- four blocks- and four -treatments, with -a total of 6 -experimentar -unjfs were used. The information gathered in the field was processed us-in9 SPSS t9st-atistical software; which- uses- the- P-value -comparison -signifamt at confidence fevels of -0.--05 and 0.-01 differences in the anatysis of variance (ANOVA} and- mutttple- range test· of- Duncan P ~ 0:05-. The variables evatoated were: tettuce tiead diameter (cm), root féngth (cm), ptant height (cm), plant weight (g), number of teaves per plant, yiek:l in kg ha-t, and economrc ana1ysis. Plarrting was done direct1y and was peñormed at the begjnning_ of each moon phase, being ptanted in the phase of New Moon on 27/09/'ff; at Futf Moon Day 0411011.1, last Quarter on.1.211-0111 and. New Maan,. on 20110111. .. The results indicate that the fulf moon phase treatment was scored the rughest yiefd of feaves wUh 57,300 kg ha-1 and which produced most oost effective, generating-more profit;_ with a value of 5.68, respectjvely. -K-eywof'ds: phases, Moon, New, phase of New Moon, Full Moon Oay, and last Quarter; cost, leaves, growing, tettuce, variety: